2016
DOI: 10.1016/j.vetmic.2016.09.019
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of alcelaphine herpesvirus-1 (AlHV-1) immunization with the adjuvants Emulsigen ® and the monomeric TLR5 ligand FliC in zebu cattle against AlHV-1 malignant catarrhal fever induced by experimental virus challenge

Abstract: HighlightsVaccination induces a pharyngeal antibody response in shorthorn zebu cross (SZC).Direct challenge with the AlHV-1 virus is effective at inducing MCF in SZC.Attenuated AlHV–1 + Emulsigen® vaccine efficacy in SZC calculated to be 50%.Bacterial flagellin is not a good adjuvant as inclusion reduced antibody response.We provide evidence that non-fatal AlHV-1 infections occur in SZC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The role of antibodies induced by vaccination in protection against MCF have been demonstrated in previous studies using an attenuated AlHV-1 vaccine [ 27 , 28 , 29 , 30 , 31 ]. Although results vary depending on animal breed, the adjuvant used, and the experimental design, overall, high levels of vaccination-induced specific antibodies in the respiratory tract and blood are associated with protection following challenge.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The role of antibodies induced by vaccination in protection against MCF have been demonstrated in previous studies using an attenuated AlHV-1 vaccine [ 27 , 28 , 29 , 30 , 31 ]. Although results vary depending on animal breed, the adjuvant used, and the experimental design, overall, high levels of vaccination-induced specific antibodies in the respiratory tract and blood are associated with protection following challenge.…”
Section: Discussionmentioning
confidence: 91%
“…Alternatively, adjuvants may also be used to increase vaccine efficacy. It has been shown with the attenuated AlHV-1 vaccine for wildebeest-associated-MCF that delivery of the vaccine in Emulsigen ® (MVP Adjuvants) is critical to induce protective antibody responses [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Malignant catarrhal fever is a fatal disease for cattle, the last hosts of this infection. Although experimental vaccine studies have been reported for cattle (Haig et al 2008 ; Lankester et al 2016 ; Russel et al 2012 ), there is no commercial product available in common use because of an insufficient antibody response in terms of intensity and duration. Prevention of MCF has classically focused on control of transmission of OvHV-2 between sheep and cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Alcelaphine herpesviruses 1 and 2 are the only Macaviruses that can currently be propagated in culture [13] , [14] , although AlHV-2 was considered non-pathogenic in cattle, leading to the preferential use of AlHV-1 over OvHV-2 to study the pathogenesis and control of MCF [15] , [16] , [17] , [18] , [19] , [20] , [21] . Pathogenic AlHV-1 can be propagated in a cell-associated form in bovine primary epithelial cells but after several passages the virus becomes culture-adapted and releases cell-free virus into the culture medium [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%